A reputation management plan for public officials - Malalis, Francis Lyn C.
This study was primarily conducted in order to provide public officials a comprehensive plan which will enable to mitigate a crisis situation. The main goal of the plan was to manage or even improve the reputation of public officials in Davao City if ever they will be faced with crisis in the future. This goal was in adherence to the premise that the reputation of a public figure is crucial in a crisis situation; the need to craft a Reputation Management Plan. The literature of the study made the plan valid by establishing the fact that crisis is a natural phenomenon. Also, the literature proved the practicability of Dave Fleet's Content of a Communication Plan which was used as the template for this study. There were two faces in the study: the first and the second phases. The first phase dealt with the research part. It used Mayor Sara Duterte-Carpio's punching incident as its sample crisis situation. It was first juxtaposed to Smith's Three- Step Model which proved the existence of a crisis in the sample crisis situation. Then the survey commenced. It was conducted to the student leaders of the three randomly chosen secondary schools in Pagadian City and its result showed that the mayor's reputation was tarnished. Hence, this served as an impetus for this study's second phase which was the formulation of the plan. The plan was the summative phase of this study. It involved specific steps in order to manage public officials' reputation during a crisis. It incorporated the results in the survey and it used RA6713 or the Code of Conduct and Ethical Standards for Public Officials and Employees as its legitimate basis. Further, it used several interpersonal communication tactics and public relations strategies in order to achieve its objectives. The plan strategies and techniques may still be applied to other places despite the fact that the plan was specifically crafted for public officials in Davao City and its neighboring places. In some cases, it may need to be enhanced to suit crises outside Davao City. The researcher came to a conclusion that though it is indeed a fact that crisis is inevitable and that it really happens at basically no preferred time, it is always possible to mitigate the situation and lessen or limit the damages it nay cause, specifically on the reputation of the public official in crisis ? exactly the core of this study, the Reputation Management Plan
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication